PENGALAMAN PELANGGAN MEMBELI TIKET KONSER COLDPLAY: MENAMBANG ULASAN ONLINE BERDASARKAN PEMODELAN TOPIK DAN ANALISIS SENTIMEN - Zahra, Denada Fatimah; Carkiman, Carkiman (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This study aims to analyze customer experience in buying tickets for the Coldplay Concert in Indonesia using sentiment analysis and topic modelling. Data is collected from online customer reviews about concert ticket purchases via social media platforms such as Twitter. The stages of the research include data collection, data labelling, data pre-processing, topic modelling using Latent Dirichlet Allocation (LDA), sentiment analysis, and interpretation of the results. The results of the sentiment analysis show that most reviews are positive, with customers expressing satisfaction with the ticket-buying process, experience at the concert, Coldplay's performance, and customer service. Several primary topics frequently appearing in reviews have been identified through topic modelling, including ticket-buying, concert experience, ticket prices, customer service, concert performance, concert location, togetherness with fans, accessibility, concert facilities, and supporting events. The interpretation of each topic provides insight into customer preferences and expectations. Recommendations for concert organizers include improving customer service, ensuring performance quality, choosing a convenient concert location, and paying attention to accessibility and the atmosphere around the concert venue. This research provides an in-depth understanding of customer experience and can serve as a guide for concert organizers to improve customer experience in the future.